Европейская бизнес-ассоциация в системе международных неправительственных экономических организаций - Штуца, Виктор Николаевич; Штуца, Віктор Миколайович; Shtuca, V. (My University, 2013)
The article deals with the role of international non-governmental economic organizations in contemporary economic relations on the example of the European Business Association. Indicate the status and structure of the European Business Association in Ukraine, analyzed the basic forms and directions of its activities.
Штуца В. Н. Европейская бизнес-ассоциация в системе международных неправительственных экономических организаций / В. Н. Штуца // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОН України ; НУ ОЮА. – Одеса : Фенікс, 2013. – Вип. 48. – С. 120-130.
Keywords: международные неправительственные экономические организации; Европейская бизнес-ассоциация; статус Европейской бизнес-ассоциации в Украине; структура Европейской бизнес-ассоциации в Украине; формы и направления деятельности Европейской бизнес-ассоциации в Украине; міжнародні неурядові економічні організації; Європейська бізнес-асоціація; статус Європейської бізнес-асоціації в Україні; структура Європейської бізнес-асоціації в Україні; форми і напрямки діяльності Європейської бізнес-асоціації в Україні; international non-governmental economic organizations; European Business Association; the status of the European Business Association in Ukraine; the structure of the European Business Association in Ukraine; shape and direction of the European Business Association in Ukraine